MODELING THE IMPACT OF ELECTRICITY PRODUCED BY THE KUDASH HYDROPOWER PLANT ON NETWORK OPERATION MODES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This study explores the impact of electricity produced by the Kudash Hydropower Plant on the operational modes of Uzbekistan’s national power grid. With the increasing importance of renewable energy sources, particularly hydropower, in modernizing energy systems, understanding their effects on grid stability and efficiency is crucial. The research employs dynamic simulation models and machine learning algorithms to predict fluctuations in electricity demand and optimize hydropower output. The study highlights the significant role of hydropower plants like Kudash in stabilizing the grid during peak demand periods by adjusting energy production in real-time. Through advanced forecasting techniques, such as Artificial Neural Networks (ANNs) and Support Vector Machines (SVMs), the research provides valuable insights into improving load forecasting, enhancing grid management, and optimizing hydropower integration into the national grid. The findings have important practical implications for Uzbekistan's energy sector, especially given the country’s renewable energy strategy outlined in the Presidential Decree (No. PP-4928, 2021). This study offers a comprehensive framework for integrating hydropower into national grids, ensuring energy stability and efficiency in line with global sustainability goals.